Structural basis for osmotic regulation of the DNA binding properties of H-NS proteins. Issue 4 (11th January 2020) - Qin, Liang; Bdira, Fredj Ben; Sterckx, Yann G J; Volkov, Alexander N; Vreede, Jocelyne; Giachin, Gabriele; van Schaik, Peter; Ubbink, Marcellus; Dame, Remus T
Abstract: H-NS proteins act as osmotic sensors translating changes in osmolarity into altered DNA binding properties, thus, regulating enterobacterial genome organization and genes transcription. The molecular mechanism underlying the switching process and its conservation among H-NS family members remains elusive. Here, we focus on the H-NS family protein MvaT from Pseudomonas aeruginosa and demonstrate experimentally that its protomer exists in two different conformations, corresponding to two different functional states. In the half-opened state (dominant at low salt) the protein forms filaments along DNA, in the fully opened state (dominant at high salt) the protein bridges DNA. This switching is a direct effect of ionic strength on electrostatic interactions between the oppositely charged DNA binding and N-terminal domains of MvaT. The asymmetric charge distribution and intramolecular interactions are conserved among the H-NS family of proteins. Therefore, our study establishes a general paradigm for the molecular mechanistic basis of the osmosensitivity of H-NS proteins.